Gromadzenie i ochrona źródeł szkolnych - Wróblewska, Urszula (Biuletyn Historii Wychowania, 2017)
Among the historical information on the development of education and upbringing in Poland, it is the school sources that have cognitive value. The school sources include chronicles, official documents, photographs, interviews, school diaries, school newspapers, school equipment, and exhibits in school memorial rooms. Since the school sources have been present as long as the schools themselves, they provide the most accurate information about the activities of schools. Usually, the school documentation duty was imposed by the school authorities, which developed appropriate regulations, and with time the systems for protection of school resources were also implemented. The school authorities also designed detailed guidelines for the preparation of, inter alia, school chronicles, and encouraged employees to write them. The interest in school documentation especially grew in the Second Republic of Poland, which resulted from the process of rebuilding the administrative structures of the Polish state. All documents were subject to an assessment by the School Inspector. The process of creating school documentation was accompanied by initiatives to store and protect it. Pedagogues started to create school museums, where the school documents were to be kept. School sources meet the criteria of historical sources. However, it is difficult to suggest a uniform typology of school sources, as it depends on the definition of the source. School source materials of invaluable cognitive value and a rich iconographic base might be the basis for research in history, education science, ethnology, sociology and anthropology. Despite their cognitive value, the school sources are currently not protected by law and may become dispersed and irreversibly lost.